2022
DOI: 10.1007/s12369-022-00935-5
|View full text |Cite
|
Sign up to set email alerts
|

Does the Personality of Consumers Influence the Assessment of the Experience of Interaction with Social Robots?

Abstract: In recent years, in response to the effects of Covid-19, there has been an increase in the use of social robots in service organisations, as well as in the number of interactions between consumers and robots. However, it is not clear how consumers are valuing these experiences or what the main drivers that shape them are. Furthermore, it is an open research question whether these experiences undergone by consumers can be affected by their own personality. This study attempts to shed some light on these questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Regarding personality traits, the current study focuses on conscientiousness as one dimension of the Big Five personality traits, and personal innovativeness, both of which are relevant to the adoption of technological innovation. Earlier studies have identified that acceptance intention toward robots is significantly influenced by conscientious (e.g., Forgas-Coll et al, 2022) and personal innovativeness (e.g., Sung & Jeon, 2020). Additionally, Yeh et al (Yeh 2021) reported that among the Big Five personality traits, conscientious was the only predictor for motivations associated with the acceptance of learning technology adoption.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding personality traits, the current study focuses on conscientiousness as one dimension of the Big Five personality traits, and personal innovativeness, both of which are relevant to the adoption of technological innovation. Earlier studies have identified that acceptance intention toward robots is significantly influenced by conscientious (e.g., Forgas-Coll et al, 2022) and personal innovativeness (e.g., Sung & Jeon, 2020). Additionally, Yeh et al (Yeh 2021) reported that among the Big Five personality traits, conscientious was the only predictor for motivations associated with the acceptance of learning technology adoption.…”
Section: Introductionmentioning
confidence: 98%
“…To examine how parents intend to behave regarding the use of AI-based social robots, previous studies on technology acceptance that highlight individual motivations, personality traits and perceptions of technology are essential. For example, some researchers have explored the influences of utilitarian and hedonic motivations on adopting or using technology (e.g., Akdim et al, 2022;Keszey, 2020); others have focused on the impact of personality traits (e.g., conscientiousness: Ma Dangi & Mohamed Saat, 2021;Forgas-Coll et al, 2022;personal innovativeness: Jackson et al, 2013;Kim, 2016;Sung & Jeon, 2020) . These studies have verified the significance of the aforementioned variables in the adoption or use of technology.…”
Section: Introductionmentioning
confidence: 99%